2021
DOI: 10.1007/s00125-021-05635-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ethnic GWAS and fine-mapping of glycaemic traits identify novel loci in the PAGE Study

Abstract: Aims/hypothesis Type 2 diabetes is a growing global public health challenge. Investigating quantitative traits, including fasting glucose, fasting insulin and HbA 1c , that serve as early markers of type 2 diabetes progression may lead to a deeper understanding of the genetic aetiology of type 2 diabetes development. Previous genome-wide association studies (GWAS) have identified over 500 loci associated with type 2 diabetes, glycaemic traits and insulin-related traits. However, most of these findings were bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Notable allele frequency distribution has been observed in BMI-associated variants which consequently confers ancestral differences in BMI. For example, in a transancestry meta-analysis by Downie et al, wide variation of minor allele frequency (MAF) was seen across populations for sentinel variants ranging from 0.12-0.36 for VEGFA locus and 0.10-0.37 for PTEN locus (Downie et al, 2022). A population specific locus (LRRC37A5P) was found in individuals that self-identify as African Americans (Downie et al, 2022).…”
Section: Bmimentioning
confidence: 99%
See 1 more Smart Citation
“…Notable allele frequency distribution has been observed in BMI-associated variants which consequently confers ancestral differences in BMI. For example, in a transancestry meta-analysis by Downie et al, wide variation of minor allele frequency (MAF) was seen across populations for sentinel variants ranging from 0.12-0.36 for VEGFA locus and 0.10-0.37 for PTEN locus (Downie et al, 2022). A population specific locus (LRRC37A5P) was found in individuals that self-identify as African Americans (Downie et al, 2022).…”
Section: Bmimentioning
confidence: 99%
“…For example, in a transancestry meta-analysis by Downie et al, wide variation of minor allele frequency (MAF) was seen across populations for sentinel variants ranging from 0.12-0.36 for VEGFA locus and 0.10-0.37 for PTEN locus (Downie et al, 2022). A population specific locus (LRRC37A5P) was found in individuals that self-identify as African Americans (Downie et al, 2022). The identification of these ancestry specific loci underscores the significance of undertaking genetic studies in diverse populations.…”
Section: Bmimentioning
confidence: 99%
“…Over the last years, consortium-driven genome-wide association studies (GWAS) have successfully identified common variants at genomic loci associated with an increased risk of T2D [ 36 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ]. A few of the coding variants identified in these studies result in hypomorphic variants [ 9 , 190 ].…”
Section: Genetic Basis Of β Cell Dysfunctionmentioning
confidence: 99%
“…In sex-combined studies, SNPs in the adenylate cyclase 5 (ADCY5 ) gene are associated with multiple T2D-related traits including FG ( 23 , 28 32 ), FI ( 21 ), glycated hemoglobin ( 33 ), HOMA-B (i.e., index of insulin secretion) and T2D ( 34 43 ), anthropometric and body fat distribution traits, such as WHR ( 44 , 45 ), body fat percentage ( 46 ), BMI ( 47 ), inflammation phenotypes such as C-reactive protein ( 48 ), early life factors including gestation duration ( 49 ), birth weight ( 50 56 ), blood lipid levels, including total cholesterol ( 57 , 58 ), HDL-cholesterol, apolipoprotein A1 ( 59 ), and blood pressure measures ( 60 ). SNPs in the vicinity of ADCY5 showed sex-dimorphic effects in association to FG.…”
Section: Human Genes/loci With Sex-dimorphic Effects On Glucose Relat...mentioning
confidence: 99%
“…The melatonin receptor 1B ( MTNR1B ) gene is a well-established T2D locus with significant associations with multiple glucose-related traits including FG ( 21 , 23 , 28 30 , 67 , 94 101 ), glycated hemoglobin ( 31 33 , 102 , 103 ), insulin levels, insulin disposition index and insulin secretion rates ( 104 , 105 ), acute insulin response, HOMA-B ( 21 ), and T2D ( 27 , 34 , 35 , 37 40 , 42 , 43 , 106 , 107 ). The gene is also associated with various sleep and circadian rhythm-related phenotypes ( 108 , 109 ).…”
Section: Human Genes/loci With Sex-dimorphic Effects On Glucose Relat...mentioning
confidence: 99%